ETHNO PEDAGOGICAL PREPARATION AS AN IMPORTANT FACTOR OF DEVELOPMENT OF NATIONAL SELF-CONSCIOUSNESS OF A FUTURE TEACHER - Sakhipzhamal, Uzakbaeva; Alma, Aitbaeva; Gulshat, Bakhtiyarova; Ryszhan, Rysbekova; Zhanna, Akparova (International Journal of Psychosocial Rehabilitation, 2020)
The ethno pedagogical preparation of the future teacher acts as part of a holistic pedagogical process in which the unity of the content, forms, means and methods of education stimulates the spiritual development of future specialists, whose main tasks are the formation of a basic ethnopedagogical culture, the development of the ability to perceive the traditional pedagogical culture, the popular experience of upbringing, and instilling national identity, high spiritual needs and interests, improving the culture of communication, Maintenance of its place in the dialogue of cultures. These qualities are developed not from outside, but as a result of pedagogical activity at the university, directed by the teacher.